2015
DOI: 10.1093/jxb/erv192
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged expression of the BX1 signature enzyme is associated with a recombination hotspot in the benzoxazinoid gene cluster in Zea mays

Abstract: HighlightHigh transcript levels of the signature gene Bx1 increase concentrations of the defence compound DIMBOA in older maize, and cis-elements upstream of Bx1 are required for high mRNA levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
78
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 56 publications
6
78
0
Order By: Relevance
“…B97 inbred line developed from Iowa Corn Borer Synthetic population showed to be resistant to European corn borer (Ostrinia nubilalis Hüber) (Abel et al, 2000). This inbred line, together with Mo17 and M37W, possess aphid resistance and high DIMBOA concentration even in later developmental stages (Zheng et al, 2015). This finding is in line with the study of Betsiashvili et al (2015) with near-isogenic lines revealing that increased DIMBOA accumulation is positively associated with Mo17 allele, contrarily to the B73 allele.…”
Section: Resultssupporting
confidence: 89%
“…B97 inbred line developed from Iowa Corn Borer Synthetic population showed to be resistant to European corn borer (Ostrinia nubilalis Hüber) (Abel et al, 2000). This inbred line, together with Mo17 and M37W, possess aphid resistance and high DIMBOA concentration even in later developmental stages (Zheng et al, 2015). This finding is in line with the study of Betsiashvili et al (2015) with near-isogenic lines revealing that increased DIMBOA accumulation is positively associated with Mo17 allele, contrarily to the B73 allele.…”
Section: Resultssupporting
confidence: 89%
“…For example, bx1 (benzoxazinless1), which encodes an indole-3-glycerol phosphate lyase, was within a QTL for the level of 2,4-dihydroxy-7-methoxy-1,4-benzoxazin-3-one (DIMBOA), and this QTL was identified in both experiments in the ZY population (Table II). DIMBOA is the main benzoxazinoid in maize that confers resistance to herbivores and microbes, and bx1 is a signature gene in the DIMBOA biosynthetic pathway (Meihls et al, 2013;Zheng et al, 2015).…”
Section: Cross-validation Of Metabolic Qtls and Identification Of Canmentioning
confidence: 99%
“…The inbred lines of tropical origin showed higher content of HDMBOA comparing to DIMBOA, while in modern temperate lines the ratio between these BXs was opposite (Meihls et al, 2013). Three inbred lines, namely Mo17, B97 and M37W, were identified for aphid resistance and high DIMBOA concentration of 1.5 mM or more in later developmental stages (Zheng et al, 2015). The study of Betsiashvili et al (2015) confirmed that the Mo17 allele caused increased DIMBOA accumulation.…”
mentioning
confidence: 76%
“…One such example is the susceptibility of maize to the second generation to ECB, which causes more severe damages to the crop comparing to the first generation. Surprisingly, however, a recent finding elucidated the mechanism for prolonged biosynthesis of DIMBOA in later developmental stages of the maize inbred line Mo17 (Zheng et al, 2015). A cis-element, called DICE, located upstream of Bx1 gene, was found to be required for high DIMBOA content and independent of Bx1 transcription.…”
mentioning
confidence: 97%